Sixty Years on the Margin: The Evolution of Ontario’s Tree Planting Industry and Labour Force: 1945–2007 - Sweeney, Brendan (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2009)
Abstract This paper examines the evolution of Ontario’s tree planting industry and the segmentation of its labour force since the end of World War II. To do so, it draws upon Jamie Peck’s causal emphases of labour market segmentation: labour demand, labour supply, and the state. Concomitantly, it seeks to better conceptualize tree planting amongst other forestry and seasonal natural resource occupations, such as loggers and agricultural workers. The paper is organized around four distinct time periods, all of which are marked by significant changes to the structure and political economy of the forest products industry and legislation governing forest tenure and management. It also examines mechanization in the logging and tree planting industries, the shift from public to private service delivery, the role of unions, remuneration systems, the potential for the use of migrant guest workers, and the ensuing eﬀects on the segmentation, marginalization, and stigmatization of tree planters in Ontario since the mid-1940s.